The Beta Agonist Lung Injury TrIal (BALTI)--prevention trial protocol. - Perkins, G; Park, D; Alderson, D; Cooke, M; Gao, F; Gates, S; Lamb, S; Mistry, D; Thickett, DR (2011)
BACKGROUND: Acute lung injury complicates approximately 25-30% of subjects undergoing oesophagectomy. Experimental studies suggest that treatment with beta agonists may prevent the development of acute lung injury by decreasing inflammatory cell infiltration, activation and inflammatory cytokine release, enhancing basal alveolar fluid clearance and improving alveolar capillary barrier function. METHODS/DESIGN: The Beta Agonist Lung Injury TrIal (prevention) is a multi-centre, randomised, double blind, placebo-controlled trial. The aim of the trial is to determine in patients undergoing elective transthoracic oesphagectomy, if treatment with inhaled salmeterol 100 mcg twice daily started at induction of anaesthesia and continued for 72 hours thereafter compared to placebo affect the incidence of early acute lung injury and other clinical, resource and patient focused outcomes. The primary outcome will be the development of acute lung injury within 72 hours of oesophagectomy. The trial secondary outcomes are the development of acute lung injury during the first 28 days post operatively; PaO2: FiO2 ratio; the number of ventilator and organ failure free days, 28 and 90 day survival; health related quality of life and resource utilisation. The study aims to recruit 360 patients from 10 UK centres. TRIAL REGISTRATION NUMBER: Current Controlled Trials ISRCTN47481946.